The impact of work stress to job burnout among employees in the Malaysian construction companies - Hu, Xiaojie; Diyana, Kamarudin; Yasmin, Hussain; Siti Hazelin, Mustafa (Turkish Journal of Physiotherapy and Rehabilitation, 2021)
The impact of stress from factors such as absenteeism, work load, work-life balance, and work stress on job burnout among employee has been widely discussed. Job burnout can affect both physical and mental health which often leads to low productivity and job performance. The purpose of this study is to examine the relationship and impact between absenteeism, work-load, work-life balance, and work-stress with job burnout. The objective includes assessing the model fit and statistically significant indicator detection. 123 construction companies were sampled using simple random sampling. Data were collected through questionnaires. Results showed adequate fit of a PLS-SEM model, and indicators of absenteeism and work stress were statistically significant on job burnout. The implications of this study is that burnout could affect employee productivity and performance. Burnout is also a serious concern within the healthcare industry as it could affect a person’s mental and physical well-being.